2023
DOI: 10.1111/ele.14322
|View full text |Cite
|
Sign up to set email alerts
|

Tropical and temperate differences in the trophic structure and aquatic prey use of riparian predators

Liam N. Nash,
Pavel Kratina,
Fátima C. Recalde
et al.

Abstract: The influence of aquatic resource‐inputs on terrestrial communities is poorly understood, particularly in the tropics. We used stable isotope analysis of carbon and nitrogen to trace aquatic prey use and quantify the impact on trophic structure in 240 riparian arthropod communities in tropical and temperate forests. Riparian predators consumed more aquatic prey and were more trophically diverse in the tropics than temperate regions, indicating tropical riparian communities are both more reliant on and impacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…Another meta‐analysis found that aquatic insect emergence patterns vary with latitude, being seasonally constrained with small aseasonal fluctuations in the tropics to large seasonal peaks at the highest latitudes (Nash, Zorzetti, et al., 2023). Indeed, a more consistent flux of allochthonous resources could lead to consumer communities that are more reliant on and impacted by them, which is what a companion study that compared riparian spiders in tropical and temperate zones found (Nash, Kratina, et al., 2023).…”
Section: Discussionmentioning
confidence: 87%
“…Another meta‐analysis found that aquatic insect emergence patterns vary with latitude, being seasonally constrained with small aseasonal fluctuations in the tropics to large seasonal peaks at the highest latitudes (Nash, Zorzetti, et al., 2023). Indeed, a more consistent flux of allochthonous resources could lead to consumer communities that are more reliant on and impacted by them, which is what a companion study that compared riparian spiders in tropical and temperate zones found (Nash, Kratina, et al., 2023).…”
Section: Discussionmentioning
confidence: 87%